Comparing Influenza and Rsv Viral and Disease Dynamics in Experimentally Infected Adults Predicts Clinical Effectiveness of Rsv Antivirals. Issue 6 (August 2013) - Bagga, Bindiya; Woods, Christopher W; Veldman, Timothy H; Gilbert, Anthony; Mann, Alex; Balaratnam, Ganesh; Lambkin-Williams, Robert; Oxford, John S; McClain, Micah T; Wilkinson, Tom; Nicholson, Brad P; Ginsburg, Geoffrey S; et al.
Background: Antivirals reduce influenza viral replication and illness measures, particularly if initiated early, within 48 h of symptom onset. Whether experimental antivirals that reduce respiratory syncytial virus (RSV) load would also reduce disease is unknown. This study compares viral and disease dynamics in humans experimentally infected with influenza or RSV. Methods: Clinical strains of RSV-A and influenza A were inoculated intranasally into 20 and 17 healthy volunteers, respectively, on day 0. Symptom scores and nasal washes were performed twice daily, and daily mucus weights were collected. Viral loads in nasal washes were quantified by culture (plaque assay in HEp-2 cells for RSV and by end point dilution in Madin–Darby canine kidney cells for influenza). Results: After influenza inoculation, influenza viral load and illness markers increased simultaneously until day 2. Within individual subjects, peak influenza load occurred 0.4 days (95% CI -0.4, 1.3) before peak symptoms. Influenza viral load and disease declined thereafter. After RSV inoculation, a longer incubation period occurred prior to viral detection and symptom onset. RSV load and disease increased together until day 5. Within individual subjects, peak RSV loads occurred 0.2 days (95% CI -0.7, 1.05) before peak symptoms, after which both illness measures and viral load declined together. Conclusions: Viral and disease dynamics in experimental human infections suggest that reducing RSV load, if timed similarly to clinically-effective influenza antivirals, might be expected to have a similar or greater window of opportunity for reducing clinical RSV disease.